Construction of OH-functionalized MWCNT/solid waste composites with tubular/spherical heterostructures for enhanced electromagnetic wave absorption property. Issue 25 (27th May 2022) - Liu, Mengzhu; Wang, Hongwei; Lv, Yangyang; Zhang, Yingyuan; Wang, Yongpeng; Zhang, Haibo; Jiang, Zhenhua
Abstract : Novel MWCNT/FAC composites based on a tubular/spherical micro–nano structure system are designed and prepared through physical mixing for achieving enhanced EWA property. Abstract : Electromagnetic wave (EMW) absorption materials with high efficiency and simple preparation process are highly desirable for practical applications. However, there are still many obstacles to simultaneously satisfy the practical requirements. Herein, fly ash cenospheres (FACs), solid waste from power plants, were selected as a framework to prepare OH-functionalized multi-walled carbon nanotube (MWCNT)/FAC hybrids with multilayer, connected and porous architectures via a facile physical mixing process for the first time. Accordingly, a novel tubular/spherical model for EMW absorption materials was established. The effect of the unique heterostructure, which possessed multiple interfaces, on the EMW absorption property was studied. The results indicated that this structure is conducive to extending the transmission route, adjusting the conductivity and improving the dielectric loss. Thus, the composite showed an excellent EMW absorption performance. The minimum reflection loss of −44.67 dB occurs at 4.9 GHz and the effective bandwidth below −10 dB (90% attenuation of EMW) could shift from 4.1 to 19.2 GHz with a thickness in the range of 1.5–5.5 mm. The superior absorption property is mostly attributed to the synergistic effect of good impedance matching, multiple loss mechanisms, and multiple reflections and scatterings. Thus, this product meets the requirement of high absorption performance and simple preparation, which greatly enhance its applicability.